A more accurate method acquirement by a comparison of the prediction equations for estimating glomerular filtration rate in Chinese patients with obstructive nephropathy. Issue 1 (December 2016) - Chen, Meixue; Xia, Jumei; Pei, Guangchang; Zhang, Ying; Wu, Shuting; Qin, Yushuang; Deng, Yuanjun; Guo, Shuiming; Guo, Yanyan; Xu, Gang; Han, Min
Abstract Background Researchers have developed several equations to predict glomerular filtration rate (GFR) in patients with chronic kidney diseases (CKD). However, there are scarcely any studies performed to discern the best equation to estimate GFR in patients with pure obstructive nephropathy. In present study, we assessed the suitability of six prediction equations and compared their performance in eGFR evaluation for Chinese patients with obstructive nephropathy. Methods A total of 245 adult patients with obstructive nephropathy were enrolled. We evaluated the performance of the 3 Modification of Diet in Renal Disease equations (MDRD) (the original MDRD7, 7MDRD; the abbreviated MDRD, aMDRD; and re-expressed abbreviated MDRD, re-aMDRD) and 3 Chronic Kidney Disease Epidemiology Collaboration equations (CKD-EPI) (CKD-EPI equation based on creatinine alone, CKD-EPIcr; CKD-EPI equation based on cystatin C alone, CKD-EPIcys; CKD-EPI equation based on combined creatinine-cystatin, CKD-EPIcr-cys). The measured GFR (mGFR) by99 mTc-DTPA renal dynamic imaging method was used as the reference GFR. Results The mean age of the study population was 51.61 ± 14.17 and 131 were male (53.47 %). The mean measured GFR was 66.54 ± 23.99 ml/min/1.73 m2 . Overall, the CKD-EPIcr-cys equation gave the best performance with the best correlation (R = 0.72) and agreement (−34.87, 40.83). CKD-EPIcr-cys equation also exhibited the highest accuracy (69.39 %, P < 0.01) and diagnostic efficacy (ROCAUC = 0.874) with the smallest bias (2.98, P < 0.01). In the subgroup of the lowest GFR, CKD-EPIcys equation exhibited the highest accuracy (52.69 %) and the smallest bias (0.27). In the youngest age subgroup, CKD-EPIcys equation had the highest accuracy (71.64 %) and the smallest bias (−1.24). In other subgroups stratified by GFR, age and gender, CKD-EPIcr-cys equation remained the best performance. Conclusion The 3 CKD-EPI equations performed better than the 3 MDRD equations in estimating GFR in Chinese obstructive nephropathy patients; while the CKD-EPI equation based on combined creatinine-cystatin C provided the best estimation of GFR.